Determinants of Consumer Decisions to Adopt Islamic Banking Services in Indonesia - Sudarsono, Heri; Afandi, Akhsyim; Perdana, Andika Ridha Ayu (Univeristas Islam Bandung, 2023)
This study examines the influence of attitudes, subjective norms, perceived behavior control, and religiosity on consumer intention to adopt Islamic bank services. This study used 550 respondents from 26 provinces in Indonesia. The study develops a structural equation model (SEM) to achieve its purpose. The results show that attitudes, subjective norms, and perceptions of behavioral control affect people's interest in adopting Islamic banking services. Likewise, awareness, uncertainty, suitability, and relative advantage, affect the intention of the consumer to adopt Islamic banks' services. In contrast, religiosity does not affect community interest in adopting Islamic bank services. Further, normative beliefs affect subjective norms and self-efficacy, whereas facility conditions affect perceived behavior control of consumers' intention to adopt Islamic banking services. Attitudes, subjective norms, and perceived behavior control influence consumers' intention to adopt Islamic banking services. Accordingly, Islamic banks need to improve services to the public. Also, Islamic banks need to increase their understanding of religious religiosity to foster interest in adopting Islamic bank services